2013
DOI: 10.1002/j.1532-2149.2013.00397.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological and psychological predictors of visceral pain sensitivity in healthy premenopausal women

Abstract: Similar to findings in patients with functional GI symptoms, we showed that subclinical GI symptoms predict visceral pain sensitivity. In line with somatic pain findings, state but not trait anxiety was found to predict visceral pain sensitivity. Our finding on serum cortisol as positive predictor of pain sensitivity might be interpreted in light of immunosuppressive effects of cortisol. Our finding on the role of IL-6 in GI symptoms is promising for understanding GI complaints in patients and needs further in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 36 publications
3
37
0
Order By: Relevance
“…Recent studies have identified cortisol as a positive predictor of pain sensitivity (28). Cortisol levels correlate negatively with pain thresholds during stress (29), potentially explaining the high incidence of pain in CD.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified cortisol as a positive predictor of pain sensitivity (28). Cortisol levels correlate negatively with pain thresholds during stress (29), potentially explaining the high incidence of pain in CD.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria encompassed any known medical conditions including gastrointestinal, neurological, psychiatric, or endocrinological disturbances and chronic medication use (except hormonal contraceptives, thyroid medications or occasional use of over‐the‐counter allergy or pain medications). Symptoms indicative of any functional or organic gastrointestinal condition were ruled out based on a standardized in‐house questionnaire . All participants were digitally evaluated for perianal tissue damage (i.e., painful hemorrhoids) potentially interfering with balloon placement.…”
Section: Methodsmentioning
confidence: 99%
“…Any chronic medication use was also exclusionary, except hormonal contraceptives, hormone replacement therapy, thyroid medications, or occasional use of over‐the‐counter allergy or pain medications for benign headaches, menstrual cramps, etc. Symptoms suggestive of any ongoing functional or organic gastrointestinal condition were ruled out based on self‐report and with a standardized in‐house questionnaire . In IBS patients, treated (or relatively minor) comorbid psychological or psychiatric symptoms including depressive symptoms or anxiety did not lead to exclusion.…”
Section: Methodsmentioning
confidence: 99%
“…The following validated questionnaires (all German versions) were completed: HADS for symptoms of anxiety and depression; NEO‐FFI for personality traits; Trier Inventory for Chronic Stress (TICS); SF‐12 for health‐related quality‐of‐life; and Pain‐Related Self Statement Scale (PRSS) for pain catastrophizing and coping . Frequency and severity of gastrointestinal symptoms during the past month (i.e., diarrhea, constipation, vomiting, nausea, lower abdominal pain, upper abdominal pain, heart burn, postprandial fullness, bloating, loss of appetite) were assessed with a standardized in‐house questionnaire utilizing a rating scale (0 = experience never; 1 = experience once or twice per month; 2 = experience once or twice per week; 3 = experience more than twice per week). In parallel to saliva sampling, state anxiety was assessed with the state version of the State Trait Anxiety Inventory (STAI‐S)…”
Section: Methodsmentioning
confidence: 99%